ANALISIS PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Pegawai Kantor Kecamatan se-Kabupaten Demak) - Wavi Aminda Sari; Mohklas Mohklas (Jurnal Dinamika Ekonomi & Bisnis, 2018)
This study aims to determine the effect of budget participation and clarity of budget targets on budget slack at the District Office in Demak District. This study uses primary data that is by providing questionnaire in the form of questionnaires distributed to respondents among others: sub-district, sub-district secretary, general sub-section and staffing, planning and reporting sub-division, sub-section of finance in Kecamatan Office in Demak Regency.The sample in this study was obtained by purposive sampling method. A total of 96 questionnaires were distributed to respondents, but with some obstacles there were 3 respondents who did not respond, so that only 93 questionnaires were sampled. The data obtained were then processed and analyzed as many as 93 questionnaires. The statistical method used to test the hypothesis is multiple linear regression analysis and Moderated Regression Analysis (MRA).The results of this study indicate that budgetary participation has a positive and significant effect on budgetary slack and the clarity of budget targets has a negative and significant effect on budgetary slack. While organizational commitment can moderate the positive relationship between budget participation and budgetary slack, so organizational commitment can moderate the negative relationship between clarity of budget goals and budgetary budget